Welding Robot Design with Machine Learning Based Intelligent Vision System - EREN, Berkay; Demir, Mehmet Hakan; Mıstıkoğlu, Selçuk (Intelligent Methods In Engineering Sciences, 2023)
The use of welding technologies in the manufacturing sector plays a very important role and increases its popularity thanks to developing technologies. Welding technologies are used in almost every field where production takes place, and the speed and efficiency of welding technologies have increased in these sectors in recent years. The fact that artificial intelligence techniques are at the forefront and the efficient use of these techniques together with sensors has led to development in welding technology. Thus, welding robots emerged with the support of robots with artificial intelligence techniques, and adaptive systems that can adapt to different types of workpieces working autonomously in the manufacturing sector are shaping the sector. Despite these developments, non-autonomous systems are still used today by teaching the welding points to the robots by the operators. Along with the concept robotic system to be designed and implemented within the scope of this study, it is planned to determine the welding trajectory autonomously with artificial intelligence techniques, and to perform the welding process by following the welding trajectory by the robot.